E-LEARNING IN THE LANGUAGE OF HIGHER EDUCATION: EVOLUTION AND HERMENEUTICS OF THE CONCEPT AND THE PHENOMENON - Ilya B. Gosudarev (Высшее образование в России)
The article considers the evolution of the concepts which haveled to the “electronic learning” expression emerging in the language of higher education in Russia. The analysis is performed applying thehermeneutical approach regarded as comparative interpretation of the concepts in their development. In the article the method of language expressions generating is analyzed as referred to the terms“web basedinstruction”, “distance education” and their Russian loan translations. As the resultof the research, an integrated definition of electronic learning is suggested as a pedagogical term based upon the categories of learning, instruction, training, and consulting. The problems of research of this phenomenon are outlined in the aspect of the development of the stygmergic pedagogical interactions in e-learning environments.